"NOT My Issue!!!": Teaching the Interpersonal Conflict Course - Nancy Brule; Jessica J. Eckstein (Central States Communication Association, 2019)
Students who enroll in communication courses to improve their conflict management abilities should be provided with both an understanding of, and skills pertaining to, interpersonal conflict across diverse contexts. In this article, we offer pedagogical guidance for teaching the Interpersonal Conflict course. With an emphasis on building communication skills usable in a variety of real-life situations and settings, this article includes discussion of necessary foundational concepts and applied content areas, sample application assignments, and relevant considerations for those teaching the course.